1997
DOI: 10.2337/diab.46.8.1360
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Directly Alters Lipid Partitioning in Skeletal Muscle

Abstract: Leptin, an adipocyte-derived hormone that directly regulates both adiposity and energy homeostasis, decreases food intake and appears to partition metabolic fuels toward utilization and away from storage. Because skeletal muscle expresses the leptin receptor and plays a major role in determining energy metabolism, we studied leptin's effects on glucose and fatty acid (FA) metabolism in isolated mouse soleus and extensor digitorum longus (EDL) muscles. One muscle from each animal served as a basal control. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
151
3
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 341 publications
(165 citation statements)
references
References 21 publications
10
151
3
1
Order By: Relevance
“…[56][57][58] As depicted in Figure 3, the earlier demonstrations that leptin can act directly on skeletal muscle, specifically via the long form of the leptin receptor (ObRb), to stimulate glucose utilization in a PI3K-dependent manner 59,60 and lipid oxidation via the activation of AMP-activated protein kinase (AMPK) leading to inhibition of ACCs 58,61 prompted us to investigate whether leptin could also exert direct control on thermogenesis in skeletal muscle. Using a method that involves repeated measurements of O 2 consumption in intact muscle perifused ex vivo with Krebs-Ringer buffer, we found that leptin could directly stimulate thermogenesis in skeletal muscle via ObRb, 62 and that this thermogenic effect of leptin, which requires PI3K activity (since it is inhibited by wortmannin), is potentiated by insulin, a potent activator of PI3K.…”
Section: Substrate Cycling Between De Novo Lipogenesis and Lipid Oxidmentioning
confidence: 99%
See 1 more Smart Citation
“…[56][57][58] As depicted in Figure 3, the earlier demonstrations that leptin can act directly on skeletal muscle, specifically via the long form of the leptin receptor (ObRb), to stimulate glucose utilization in a PI3K-dependent manner 59,60 and lipid oxidation via the activation of AMP-activated protein kinase (AMPK) leading to inhibition of ACCs 58,61 prompted us to investigate whether leptin could also exert direct control on thermogenesis in skeletal muscle. Using a method that involves repeated measurements of O 2 consumption in intact muscle perifused ex vivo with Krebs-Ringer buffer, we found that leptin could directly stimulate thermogenesis in skeletal muscle via ObRb, 62 and that this thermogenic effect of leptin, which requires PI3K activity (since it is inhibited by wortmannin), is potentiated by insulin, a potent activator of PI3K.…”
Section: Substrate Cycling Between De Novo Lipogenesis and Lipid Oxidmentioning
confidence: 99%
“…A requirement for AMPK activation and for entry of fatty acids through the mitochondrial b-oxidation pathway was also suggested by the fact that leptin-induced thermogenesis was inhibited either in the presence of araA (an inhibitor of AMPK) or by addition of etomoxir, an inhibitor of CPT-1. 63 In other experiments that involved interference with key control points of intermediary metabolism in order to investigate the nature of an 'apparent' link between leptin's direct effects on skeletal muscle to stimulate glucose metabolism, 58-60 lipid oxidation [57][58][59][60][61] and thermogenesis, 62 evidence emerged of a requirement for de novo lipogenesis in the mechanism by which leptin stimulates muscle thermogenesis. 63 Specifically, the direct thermogenic effect of leptin on skeletal muscle O 2 consumption was found to be completely inhibited by the addition of any one of the following compounds that would inhibit the synthesis of lipids from glucose, namely (a) 2-deoxyglucose, which interferes with glucose metabolism, (b) hydroxy-citrate, which inhibits citrate lyase and hence the conversion of citrate to acetyl-CoA and (c) cerulenin, which inhibits fatty acid synthase and hence the conversion of malonyl-CoA to fatty acids.…”
Section: Substrate Cycling Between De Novo Lipogenesis and Lipid Oxidmentioning
confidence: 99%
“…11 CPT-1 mRNA expression can be affected by nutritional states, and both fasting and fat feeding increase its expression. 12 Many circulating hormones secreted by white adipose tissue (WAT) including adiponectin 13,14 and leptin 15,16 can stimulate fatty-acid oxidation and glucose uptake. Undernutrition in early life may have long-lasting effects on the regulation of these hormones.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the importance of leptin to reproduction has been highlighted by the lack of sexual maturation in people who are genetically deficient in leptin [5] or the leptin receptor [6]. Although many of leptin's effects are centrally mediated, there is growing evidence that peripheral leptin receptors mediate leptin's proliferative effects on haemopoietic cells [7] and its anti-lipogenic effects on muscle and pancreatic islets [8,9].Because leptin has a critical role in regulating energy metabolism, adipose stores and body weight, questions have been raised concerning the control of leptin synthesis and secretion and the function of leptin in controlling satiety and food intake. Basal or fasting leptin values are higher in women than men, increase during the course of pregnancy and, in both healthy adults and those with Type II (non-insulindependent) diabetes mellitus, are strongly correlated with per cent body fat or BMI [10,11] and adipose tissue mass [12Ā±15].…”
mentioning
confidence: 99%